Networked Learning and Social Action: A social informatics perspective - Walker, Steve; Creanor, Linda (Proceedings of the International Conference on Networked Learning, 2006)
This paper considers networked learning in the context of civil society organisations concerned centrally with some form of social action. We briefly outline some recurring characteristics of learning, and in particular networked learning, interventions in such social action settings. We introduce the concept of sociotechnical interaction network from the social informatics literature and apply it to identify and to analyse three aspects of networked learning, drawing on case material from transnational trade union education. Finally we identify issues for further research highlighted by this model.